Force generation and work production by covalently cross-linked actin-myosin cross-bridges in rabbit muscle fibers. - Bershitsky, S Y (1995)
To separate a fraction of the myosin cross-bridges that are attached to the thin filaments and that participate in the mechanical responses, muscle fibers were cross-linked with 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and then immersed in high-salt relaxing solution (HSRS) of 0.6 M ionic strength for detaching the unlinked myosin heads. The mechanical properties and force-generating ability of the cross-linked cross-bridges were tested with step length changes (L-steps) and temperature jumps (T-jumps) from 6-10 degrees C to 30-40 degrees C. After partial cross-linking, when instantaneous stiffness in HSRS was 25-40% of that in rigor, the mechanical behavior of the fibers was similar to that during active contraction. The kinetics of the T-jump-induced tension transients as well as the rate of the fast phase of tension recovery after length steps were close to those in unlinked fibers during activation. Under feedback force control, the T-jump initiated fiber shortening by up to 4 nm/half-sarcomere. Work produced by a cross-linked myosin head after the T-jump was up to 30 x 10(-21) J. When the extent of cross-linking was increased and fiber stiffness in HSRS approached that in rigor, the fibers lost their viscoelastic properties and ability to generate force with a rise in temperature.